No Thermoregulatory Impairment in Skin Graft Donor Sites during Exercise-Heat Stress - Cramer, Matthew N. (Med Sci Sports Exerc, 2019)
The U.S. Army’s Standards of Medical Fitness, AR 40–501, state that “Prior burn injury (to include donor sites) involving a total body surface area of 40 percent or more does not meet the standard”. Inclusion of donor sites (sites harvested for skin grafts) in this Standard implies that thermoregulatory function is impaired within donor sites during exercise-heat stress; however, supporting evidence is currently lacking. PURPOSE: To test the hypothesis that well-healed donor and non-injured sites demonstrate similar elevations in skin blood flow and sweating during exercise-induced hyperthermia. METHODS: Twenty burn survivors (>1 year post-injury; four females) cycled for 60 min in a 39.7 ± 0.3°C and 21.1 ± 3.3% relative humidity environment at ~50% of maximal aerobic capacity. Core and mean skin temperatures were recorded throughout exercise. Skin blood flow (laser-Doppler imaging) was measured at baseline and after exercise within donor (LDF(DON)) and adjacent non-injured control (LDF(CON)) sites. At 45 min of exercise, local sweat rates (Technical Absorbents) were measured within the same donor (LSR(DON)) and non-injured (LSR(CON)) areas. RESULTS: After 60 min of exercise, core and skin temperatures reached 38.2 ± 0.4°C and 35.5 ± 1.2°C, respectively. The increase in skin blood flow from baseline to end-exercise (LDF(DON): 91.6 ± 44.5 AU; LDF(CON): 106.0 ± 61.6 AU; P = 0.17) and local sweat rates (LSR(DON): 0.46 ± 0.26 mg cm(−2) min(−1); LSR(CON): 0.53 ± 0.25 mg cm(−2) min(−1); P = 0.14) were not different between donor and non-injured control sites. CONCLUSION: Well-healed donor sites retain the ability to increase skin blood flow and sweating during exercise-heat stress, providing evidence against the inclusion of donor sites when determining whether a burn injury meets the Army’s Standards of Medical Fitness.